STRATEGI BELAJAR MENGAJAR DALAM UPAYA PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Hasbullah Hasbullah; Juhji Juhji; Ali Maksum (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
This article aims to analyze descriptively how teaching and learning strategies that can be carried out by educators in an effort to improve learning outcomes of Islamic Religious Education. The method used is a qualitative method with a literature review approach. Some primary and secondary references are taken from reputable research, books and journals. Data collection is through documentation, while data analysis uses content analysis. The results of the analysis revealed that the teaching and learning strategies of Islamic subject educators can use several learning methods. The strategy is in the conceptual position contained in the learning implementation plan. While the method is in a practical level position, where the teacher can actualize his plans into the methods he chooses such as modeling, giving advice, habituation, lectures, questions and answers, discussions, and demonstrations.